Social vulnerability, exposure to environmental risk factors, and accessibility of healthcare services: Evidence from 2, 000+ informal settlements in Argentina. (September 2022) - Palacios, Alfredo; Gabosi, Julia; Williams, Caitlin R.; Rojas-Roque, Carlos
Abstract: Globally, the question of how to improve the living standards of the inhabitants of informal settlements is a key political concern. These neighborhoods are characterized by economic vulnerability, social marginalization, and inaccessibility of basic services. The aim of this study is to provide evidence about the environmental risk factors faced by these populations in Argentina, and to identify whether their greater exposure to risk factors is associated with greater accessibility of healthcare services. We analyzed an original database that provides information about basic characteristics of the neighborhood, environmental risk factors (proximity to garbage dumps, industrial waste, and high-voltage towers), and accessibility of basic healthcare services on over 2000 informal settlements in Argentina. We calculated descriptive statistics and developed multivariate econometric models to estimate the probability of accessibility of healthcare services. On average, 31% of informal settlements were close to a garbage dump, 19% were close to a high-voltage tower, and 10% were close to industrial waste. In addition, 39% of these neighborhoods do not have a healthcare center nearby, 65% do not have an accessible hospital, and 39% are not consistently served by ambulances in the event of an emergency. The econometric estimates suggest that the accessibility of hospital healthcare service and to an ambulance service is positively associated with the age of the neighborhood, and whether the neighborhood is a slum, but there is no evidence of association with the exposure to environmental risk factors. In short, the populations living in informal settlements in Argentina are exposed to harmful environmental risk factors. Access to basic healthcare services is limited and does not reflect the elevated exposure to environmental risks. Health, environmental, and economic dimensions should be considered when designing and implementing public policies for vulnerable populations. Highlights: People in informal settlements are often exposed to environmental risk factors. Yet, in these neighborhoods, access to basic healthcare services is limited. More services are needed to respond to disproportionate exposure and advance equity.